EFEKTIFITAS PEMBINAAN NARAPIDANA TERORISME DALAM UPAYA DERADIKALISASI DI LEMBAGA PEMASYRATAKATAN - Iip Kamaludin (Al-Adl : Jurnal Hukum, 2021)
The penitentiary system is organized to treat prisoners so that they can be accepted back by the community, actively play a role in development, and live naturally as good and responsible citizens. Penitentiary plays a very strategic role in restoring the life and livelihood of prisoners of criminal acts of terrorism. Although in theory these terrorist convicts are classified as high risk criminals who did extra ordinary crimes. However, it is hoped that the correctional facility can carry out its function properly, so that the noble ideals of correctionalization can be achieved properly. This research is addressing the following issues, namely: (1) How effective is deradicalization in the correctional facilities? (2) What are the constraints in the practice of deradicalization of terrorist and the improvements that need to be made? The method used in this study is a normative legal research method with descriptive-qualitative analysis through the collection of legal materials and data using literature study and in-depth interviews. The results showed that deradicalization in correctional facility was still ineffective. There are several constraints, especially in the West Java region. While the efforts made to improve the quality of terrorist training include: Strengthening coordination between stakeholders, improving the quality of human resources, increasing the provision of facilities and infrastructure, optimizing special facilities for terrorists, optimizing the standards of guiding terrorists and protecting officers involved in the prevention of terrorism.